Antiobesity and Hepatoprotective Effects of Protein Hydrolysates Derived from Protaetia brevitarsis in an Obese Mouse Model. (27th March 2022) - Lee, Eun Hye; Chun, So Young; Yoon, BoHyun; Han, Man-Hoon; Chung, Jae-Wook; Ha, Yun-Sok; Lee, Jun Nyung; Kim, Hyun Tae; Kim, Dae Hwan; Beik, Gyung Yun; Jang, Byung Ik; Kwon, Tae Gyun; et al.
Abstract : Background . Obesity induced by excessive nutrients can cause fatty liver and metabolic dysfunction, which leads to hepatic dysfunction and local/systemic inflammatory responses. Previously, we analyzed the antioxidant, antilipotoxicity, and anti-inflammatory effects of protein hydrolysates in vitro. The aim of the present study is to investigate the antiobesity and hepatoprotective effects of protein hydrolysates derived from Protaectia brevitas (PHPB) in an obese mouse model. Methods . For this in vivo study, 40 mice were included and divided into four groups: (1) normal diet group, (2) high-fat-diet (ctrl(–)) group, (3) high-fat-diet and silymarin-treated (ctrl(+)) group, and (4) high-fat-diet and PHPB-treated group. After 6 weeks of treatment, body weight and the amount of daily food intake were observed. Moreover, the major organs and blood of animals were collected for the analysis of serum chemistry, histopathological examination, and obesity- and inflammation-related gene expressions. Results . The body weight and the amount of daily food intake significantly decreased in the PHPB-treated group compared with those in the ctrl(–) group. The levels of serum ALT, AST, ALP, creatinine, blood urea nitrogen, glucose, bilirubin, total cholesterol, TG, low-density lipoprotein, IL-6, TNF- α, and IGF-1 significantly reduced in the PHPB-treated group, whereas the serum free fatty acid, albumin, high-density lipoprotein, and adiponectin concentrations increased. In the analysis of weight of the liver, kidney, lungs, spleen, and fat tissues (from epididymal, perirenal, and mesentery tissues), the PHPB-treated group showed decreased values compared with the ctrl(–) group. In the histopathological analysis, the PHPB-treated group showed significantly reduced macrovesicular fatty change and inflammatory cell infiltration in the liver, and the size of the adipocyte in the epididymis also significantly decreased. The obesity- and inflammation-related gene (IL-6, TNF- α, IGF-1, leptin, AP2/FABP4, AMPK- α 2, β 3AR, and PPAR- γ ) expressions in the liver and epididymal adipose tissue were reduced in the PHPB-treated group. Conclusions . Overall, the results of this study suggest that the protein hydrolysates that derived from Protaectia brevitas produce antiobesity and hepatoprotective effects via anti-inflammatory activities.